PENGARUH PEMASARAN ONLINE, KONVENSIONAL, KUALITAS PRODUK BAKPIA PATHUK KENCANA TERHADAP KEPUTUSAN KONSUMEN - Arista Fajar Ningsih; Muinah Fadhilah; Agus Dwi Cahya (Value : Jurnal Manajemen dan Akuntansi, 2023)
Due to the fact that both online and traditional marketing are currently being discussed actively, the goal of this research problem is to identify which method is more developed and has a positive influence on consumer purchasing decisions. This marketing endeavor aims to learn how influential these two methods are in determining the number of purchasing decisions, the number of people who want to buy using conventional online marketing methods, and the quality of the products that are offered. To accomplish this, questionnaires will be distributed; in other words, quantitative methods will be used; buyers will directly fill out the questionnaires when they meet or via social media; and 100 people will be used as samples. Discovering the purchase decisions made by consumers and being supported by data acquired in the field based on the existing conditions and convenience may be determined by choosing whether or not the results attained are the same as those obtained via conventional online marketing. Because conventional and internet marketing work together to achieve their respective aims, the combination of the two kinds of marketing has grown to become an essential component of contemporary culture. Keywords: Online Marketing, Conventional Marketing, Consumer Decisions